Di-μ-chlorido-bis{bis[3,5-dimethylpyrazol-1-yl-κN (2))methane]iron(II)} bis[tetrachloridoferrate(III)] - Xia, HongYing (International Union of Crystallography, 2008)
In the title complex, [Fe(2)Cl(2)(C(11)H(16)N(4))(4)][FeCl(4)](2), the asymmetric unit is composed of one and a half units of [Fe(bdmpm)(2)Cl](2)(FeCl(4))(2)(bdmpm = bis(bis(3,5-dimethylpyrazol-1-yl)methane). The three independent Fe(II) atom have a distorted octahedral coordination geometry comprising two bridging chloride anions and four N atoms from two bis(3,5-dimethylpyrazol-1-yl)methane ligands. The Fe(III) atom has a tetrahedral coordination geometry comprising four chloride anions.